Pemberdayaan Guru SD dalam Membuat Konten Pembelajaran Inovatif Melalui Platform Media Sosial - Mesran, Mesran; Jaafar, Mime Azrina; Suginam, Suginam; Azni, Ayu Iryanti; Ginting, Guidio Leonarde (Jurnal Pengabdian Masyarakat Inovasi, 2026)
This community service program aimed to empower elementary school teachers in developing innovative learning content through the use of social media platforms, particularly short-video applications. The initiative was motivated by the challenges of low digital literacy among teachers and the limited use of social media as an effective learning tool. The program was implemented through workshops, hands-on content creation practices, and technical mentoring. The results indicate a significant improvement in teachers’ skills in producing social-media-based learning media, as reflected in the differences between their understanding and abilities before and after the program. Participant responses showed high levels of satisfaction, with most teachers acknowledging that the training supported their creativity and innovation in teaching. However, the program faced limitations in terms of its relatively short duration and unequal technological infrastructure across schools. These findings suggest that similar programs are highly relevant to be developed sustainably to support the improvement of teachers’ digital competencies.